Sesquiterpene lactones from Chrysolaena platensis - Pollora, Genaro Cesar (2000)
Aerial parts of Chrysolaena platensis (Spreng.) Robinson were collected at the flowering stage on December 28, 1997 in Misiones Province, Argentina. A voucher specimen (LIL 603539) is on deposit in the herbarium of the Fundación Miguel Lillo, Tucumán